Thiourea Derivatives: A Promising Class Against HIV/TB Co-Infection - Souza, Marcus Vinicius Nora de; Bispo, Marcelle de Lima Ferreira; Gonçalves, Raoni Schroeder Borges; Kaiser, Carlos Roland (IntechOpen, 2011)
None